Development of novel air electrode materials for fuel cells : solar activated fuel cells - Kolodziejczyk, Bartlomiej Piotr (2011)
Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri Fuel cells convert chemical energy directly into electrical energy and heat with high efficiency and low emission of pollutants. However, before fuel cell technology can gain a significant share of the energy market, many important issues have to be solved. These issues include many different aspects, one of them is the development of alternative materials for fuel cells. Present fuel cell prototypes very often use materials selected when fuel cells gained interest, it was more than 25 years ago. Commercialization aspects, including cost and durability, have revealed inadequacies in some of these materials. This paper describes research and its results on development of new electrode materials for fuel cells. Main interest was concentrated on conducting polymer – PEDOT, and its blends with non-conducting polymers. What more, during research some very interested properties of tested materials has been discovered. PEDOT and its blends with PBTh and PTTh can be light activated, this phenomena increases overall electrode performance when light is introduced. This leads to new types of fuel cells, a hybrid of fuel cell and photovoltaic cell. This paper summarizes research and development of this innovative and alternative materials. Now when European Union proposed energy policy for member countries, this research can have great importance for Poland as well as for other countries. Final Version of Master's Thesis